1H and 13C NMR investigation of 20‐hydroxyecdysone dioxolane derivatives, a novel group of MDR modulator agents. (2nd October 2013) - Balázs, Attila; Hunyadi, Attila; Csábi, József; Jedlinszki, Nikoletta; Martins, Ana; Simon, András; Tóth, Gábor
Abstract : The synthesis, structure elucidation and the complete 1 H and 13 C signal assignment of a series of dioxolane derivatives of 20‐hydroxyecdysone, synthesized as novel modulators of multidrug resistance, are presented. The structures and NMR signal assignment were established by comprehensive one‐dimensional and two‐dimensional NMR spectroscopy supported by mass spectrometry. Copyright © 2013 John Wiley & Sons, Ltd. Abstract : The synthesis, structure elucidation and the complete 1 H and 13 C signal assignment of a series of dioxolane derivatives of 20‐hydroxyecdysone, synthesized as novel modulators of multidrug resistance, are presented. The structures and NMR signal assignment were established by comprehensive one‐dimensional and two‐dimensional NMR spectroscopy supported by mass spectrometry.